Influence of Multi-Pass Friction Stir Processing on the Corrosion Behavior of an Al-Mg-Si Alloy. Issue 3 (5th January 2016) - Esmaily, M.; Mortazavi, N.; Osikowicz, W.; Hindsefelt, H.; Svensson, J. E.; Halvarsson, M.; Thompson, G. E.; Johansson, L. G.
Abstract : The effect of multi-pass (100% overlap) friction stir processing (FSP) on the NaCl-induced atmospheric corrosion behavior of an extruded 6005-T6 aluminum alloy has been studied. Samples were contaminated with 70 and 200 μg/cm 2 NaCl and exposed in the presence of 400 ppm CO2 for a time interval of 200–3200 h. The results showed that increasing the number of passes gives rise to several crucial changes in the microstructure of the processed regions. Gravimetric analyses and morphological inspections of the corroded samples revealed that multi-pass FSP has also a significant impact on the NaCl-induced atmospheric corrosion behavior of the FS processed samples. While increasing the number of FSP passes resulted in a reduced extent of pitting corrosion in the stir zone, it induced a significant pitting corrosion attack in the heat affected zone of the samples, which were shown to be linked to a reduction in the size of intermetallic particles in the stir zone of the multi-pass FSP specimens. The results also showed that the cathodic activity of intermetallic particles in this family of Al alloys is size-dependent.